2001
DOI: 10.1359/jbmr.2001.16.2.328
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Activation Induces Human Osteoclast Formation via Receptor Activator of Nuclear Factor κB Ligand-Dependent and -Independent Mechanisms

Abstract: In unstimulated conditions, osteoclast (OC) formation is regulated by stromal cell production of the key osteoclastogenic factors receptor activator of nuclear factor B ligand (RANKL) and macrophage colonystimulating factor (M-CSF). However, the mechanisms of accelerated osteoclastogenesis and bone loss characteristic of inflammatory conditions are poorly understood but appear to involve T cells. In addition, the mechanism by which OCs arise spontaneously in cultures of peripheral blood mononuclear cells in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 150 publications
(113 citation statements)
references
References 31 publications
2
111
0
Order By: Relevance
“…The finding of increased T cell activation and proliferation in mice with T cell-specific blockade of TGF␤ signaling is consistent with both the augmented Ag presentation observed in these transgenic mice and the direct repressive action of TGF␤ on T cell proliferation and differentiation. An expected consequence of increased T cell activation is increased production of osteoclastogenic cytokines (12,32,33). Measurements by ELISA of cytokine levels in 72-h culture media revealed that T cells derived from CD4dnTGF␤IIR mice produce significantly higher levels of TNF (Fig.…”
Section: Tgf␤ Represses T Cell Activation and Proliferation In E-replmentioning
confidence: 94%
“…The finding of increased T cell activation and proliferation in mice with T cell-specific blockade of TGF␤ signaling is consistent with both the augmented Ag presentation observed in these transgenic mice and the direct repressive action of TGF␤ on T cell proliferation and differentiation. An expected consequence of increased T cell activation is increased production of osteoclastogenic cytokines (12,32,33). Measurements by ELISA of cytokine levels in 72-h culture media revealed that T cells derived from CD4dnTGF␤IIR mice produce significantly higher levels of TNF (Fig.…”
Section: Tgf␤ Represses T Cell Activation and Proliferation In E-replmentioning
confidence: 94%
“…First-strand cDNA was synthesized from total RNA with oligo(dT) [12][13][14][15][16][17][18] primer and Revertra Ace (Toyobo) and subjected to PCR amplification with Ex Taq polymerase (Takara). The specific primer pairs and temperature conditions were as follows: for mouse RANKL cDNA amplification, forward: 5Ј-CGCTC TGTTCCTGTACTTTCGAGCG-3Ј/reverse: 5Ј-TCGTGCTCCCTCCTTT CATCAGGTT-3; denaturation at 94°C for 2 min followed by 32 …”
Section: Rt-pcr Analysismentioning
confidence: 99%
“…Osteoblasts and T cells express not only metalloproteinases but also tissue inhibitor of metalloproteinases (TIMPs) (9 -11). Osteoblasts in culture hardly release RANKL, but activated T cells in culture release a large amount of RANKL in a soluble form (6,12). Therefore, the soluble RANKL produced by activated T cells is believed to be involved in bone resorption induced by inflammation (13,14).…”
mentioning
confidence: 99%
“…The OVX mice were then treated with OP3-4 for 28 days at a dosage of 2 mg/kg/day, which is less than the optimal dose (6 mg/kg/day) based on IC 50 . In vitro, OP3-4 actively inhibited osteoclast formation at low concentration 2 M (0.015 mg/ml).…”
Section: Op3-4 Protects Mice Against Ovariectomy-associated Bone Lossmentioning
confidence: 99%